2019
DOI: 10.1002/jcb.28193
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of HDAC2 and HDAC3 via oleuropein as a potent prevention and therapeutic agent in MCF‐7 breast cancer cells

Abstract: Breast cancer is the most common malignancy in the world with the highest rate of morbidity and mortality. Due to the several side effects of chemotherapy and radiotherapy, recent studies have focused on the use of herbal medicines.Epidemiological reports have shown the inverse relationship between breast cancer risk and intake of olive. Oleuropein (OLE) is a polyphenolic compound in virgin olive oil with antineoplastic properties and it is well tolerated by humans. Recent reports have shown that OLE has effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 57 publications
(144 reference statements)
1
22
0
Order By: Relevance
“…Few studies on EVOO and epigenetic modulation have been conducted. Recent papers have reported that EVOO supplementation can modulate DNA methylation in vivo [42], and downregulate HDAC2 and HDAC3; this second effect in particular might be exerted, as newly hypothesized, by a specific compound: oleuropein [43]. On the other hand, thymoquinone is probably the main compound responsible for modulation of gene expression observed in cells treated with NG oil.…”
Section: Discussionmentioning
confidence: 81%
“…Few studies on EVOO and epigenetic modulation have been conducted. Recent papers have reported that EVOO supplementation can modulate DNA methylation in vivo [42], and downregulate HDAC2 and HDAC3; this second effect in particular might be exerted, as newly hypothesized, by a specific compound: oleuropein [43]. On the other hand, thymoquinone is probably the main compound responsible for modulation of gene expression observed in cells treated with NG oil.…”
Section: Discussionmentioning
confidence: 81%
“…Oleuropein (OLE), a natural polyphenol, has also shown potential apoptotic and anti-invasive effects on MCF-7 cells. In fact, OLE reduced neoplastic cell invasiveness and viability and at the same time induced apoptosis in MCF-7 cancer cells (48); in particular, OLE acts on cancer control by epigenetic mechanism, such as the inhibition of histone deacetylase (HDAC) (49).…”
Section: Breast Cancermentioning
confidence: 99%
“…There are several studies describing the potential role of OL in breast cancer. For example, researchers have established the beneficial effects of OL in MCF-7, MCF-10A, and MDA-MB-231 human breast cancer cells where OL was able to decrease the expression of histone deacetylase II (HDAC2), HDAC3, and HDAC4, induce apoptosis, and retard cell migration and invasion in a dose-dependent manner [88,89]. Besides, OL produced tissue inhibitors of metalloproteinases (TIMPs) overexpression and metalloproteinases (MMPs) genes down-regulation, which could help in the prevention of breast cancer metastasis [82].…”
Section: Ol-aglyconementioning
confidence: 99%